Mechanisms of spatial and temporal development of autoimmune vitiligo in tyrosinase specific TCR transgenic mice - Gregg, Randal K. (2010)
Generalized vitiligo is thought to have an autoimmune etiology, and has been correlated with the presence of CD8 T cells specific for melanocyte differentiation antigen. However, limited animal models for the disease have hampered its understanding. Thus, we generated TCR transgenic mice that recognize an epitope of the melanocyte protein, tyrosinase. These animals develop vitiligo with strikingly similar characteristics to the human disease. Vitiligo develops temporally and spatially, with juvenile lesions forming bilaterally in head and facial areas, and only arising later in the body of adult animals. Vitiligo is entirely dependent on CD8 T cells, while CD4 T cells exert a negative regulatory effect. Importantly, CD8 T cells can be pervasively present in the skin in the steady state without inducing vitiligo in most areas. This points to developmental differences in melanocyte susceptibility and/or immunological effector mechanisms over time, or in different body locations. Disease is strongly dependent on both IFNγ and CXCR3, while dependence on CCR5 is more limited, and both CCR4 and perforin are dispensable. Genetic ablation of CXCR3 or IFNγ also resulted in scarce CD8 T cell infiltration into the skin. Our results identify unexpected complexity in vitiligo development and point towards possible therapeutic interventions.